Molecular Studies on Newcastle Disease Virus Isolates in Relation to Field Vaccine Strains in Egypt (2012-2015) - Mouhamed, Amal A.; Mohamed, Moemen A.; Bakheet, Bakheet M.; El-Din, Khaled A. Aziz; Song , Chang-Seon (International Journal of Poultry Science, 2020)
Background and Objective: Newcastle disease (ND) is a highly contagious viral disease of avian species and represents a major threat to the poultry industry worldwide. Regardless of which type of vaccine is used, birds are still able to become infected by NDV and can transmit the disease to others. This study aimed to obtain improved understanding of the variety and interrelationships of NDV isolates. Materials and Methods: A total of 116 tissue/organ samples were subjected to virus isolation and pathogenicity assessment in vivo by intracerebral pathogenicity index (ICPI) determination. Molecular characterization was performed by one-step RT-PCR to obtain a 535 bp fragment, including the fusion gene cleavage site. The purified PCR products of 12 isolates were selected for DNA sequencing. Results: Nucleotide and deduced amino acid sequence analysis of the cleavage site of the F gene of all field isolates revealed the motif 112R-R-Q-R-R-F117 at the C-terminus of the F2 protein and F (phenylalanine) at the N-terminus of the F1 protein (residue 117), indicating that these strains were velogenic. The nucleotide sequence analysis revealed that our isolates showed the greatest nucleotide identities (99.3%) with the velogenic strains from Jordan, Israel and Turkey, suggesting that the virus circulating in Egypt probably extends from the Middle Eastern region. Phylogenetic analysis showed that our isolates could be classified into three genotypes (VIId, VIIa and II), indicating that VIId is the predominant circulating genotype in Egypt, where 10 isolates were clustered. One isolate for genotype VIIa and one for genotype II were also observed. A low evolution rate, with Ka/Ks ratios ranging from 0.01-0.02, indicated negative or purifying selection. The minimum evolutionary distance detected was 0.09 to genotype VIId, whereas the maximum distance was 0.21 to genotype II, from which most commercial live virus vaccine strains are derived. Conclusion: The control of NDV by vaccination still faces new challenges and evaluating the effectiveness of the current commercial vaccine strains against circulating NDV strains has become a necessity.